Correction: Automatic hoof-on and -off detection in horses using hoof-mounted inertial measurement unit sensors. - M Tijssen; E Hernlund; M Rhodin; S Bosch; J P Voskamp; M Nielen; F M Serra Braganςa (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0233266.].